La implementación del tratado internacional de recursos fitogenéticos parala alimentación y la agricultura en Costa Rica: Recomendaciones legales y de política - Cabrera Medaglia, Jorge (2020)
This article addresses the main constitutional provisions, the international instruments, and the institutional legal framework and public policies related to the conservation and sustainable use ofmangroves in Costa Rica. It concludes with a set of recommendations for the improvement of the legal system, based on the identification of the most important gaps and loopholes, and its adequate implementation.